MULTIGRAVIDA WITH UNCONTROLLED HYPERTHYROID AND BILATERAL PLEURAL EFFUSION - Sutrisno, Muhammad Al Farisi; Herlambang, Herlambang; Firmansyah, Firmansyah (Andalas Obstetrics And Gynecology Journal, 2020)
Background: Hyperthyroid is a hypermetabolic condition caused by abnormal thyroid gland function resulting in overproduction and overexpression of thyroid hormone. The prevalence of hyperthyroid during pregnancy is 0.1-0.4%, where 85% of case are presented as grave’s disease. Objective: To report the treatment of uncontrolled hyperthyroid during pregnancy.Method: Case Report Case: Ms. S, Female, 33 years old, presenting with brethlessness since 5 days before admission. Breathlessness persist and aggravated by lying down position. The patient has history of hyperthyroid since 1 years before admission. The blood pressure was 120/80 mmHg, respiration rate 28 times/min, and body temperature 36,7oC. Uterus fundal height 26 cm, cephalic presentation, fetal heart rate 130 times/min, single fetus intrauterine and alive. Laboratoric test for leukocyte: 21,300/ul, T4 level 22.8 mg/dl dan T3 level 2.9 mg/dl. The patient diagnosed with G3P2A0 31-week gestational age single alive fetus intrauterine with uncontrolled hyperthyroid and bilateral pleural effusion. Treatment consist of propylthiouracil as the drug of choice for anti-thyroidal drug, nifedipine for gestational hypertension and furosemide to treat the pleural effusion. Conclusion: History taking, physical examination, thyroid function test, and maintaining euthyroidism during pregnancy is a key to reduce the risk of maternal and fetal complication.Keywords: hyperthyroid, pregnancy , IUGR